“Diseño de un sistema de control interno aplicable al área administrativa y contable en la compañía Insernin C.A. dedicada a la producción y venta de adoquines” - Silva Velásquez, Mayra Isabel (2013)
The Company basically depends on the performance and quality of service and goods to deliver, especially in its most basic levels, does not have adequate accounting and administrative processes that will facilitate the efficient development. In the administrative area, hiring staff not provided sufficient training for assigned duties; also not periodic assessments. The functions performed by the staff are known for its experience each employee, but not because they have established procedures to define adequate control of activities.